2019
DOI: 10.4102/sajcd.v66i1.608
|View full text |Cite
|
Sign up to set email alerts
|

Responsive communication coaching for early childhood practitioners in underserved South African contexts: Clinical perspectives

Abstract: Children spend longer hours with early childhood development (ECD) practitioners who are well-placed to facilitate critical early language development. ECD classrooms include a growing number of children at risk for communication delays. Greater collaboration between speech-language therapists (SLTs) and ECD practitioners is needed. Research highlights that responsivity coaching improves communication development. Therefore, responsive communication coaching was identified as a possible approach to early commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…use of specialized equipment) (Sekerak et al, 2003). However, the research in rehabilitation favour in‐context interventions as they facilitate generalization of prior learning (Abdoola et al, 2019; Case‐Smith & O'Brien, 2009; Pratte et al, 2024). The frequency of pull‐out interventions should be questioned in childcare systems working towards inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…use of specialized equipment) (Sekerak et al, 2003). However, the research in rehabilitation favour in‐context interventions as they facilitate generalization of prior learning (Abdoola et al, 2019; Case‐Smith & O'Brien, 2009; Pratte et al, 2024). The frequency of pull‐out interventions should be questioned in childcare systems working towards inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in their introduction, many authors indicated that pull‐out interventions are no longer the best choice for intervening with young children. In fact, they reported a paradigm shift that now favours working directly with early childhood educators or offering in‐context interventions to children to allow for more generalization of the abilities developed by the child (Abdoola et al, 2019; Black, 2008; Dinnebeil et al, 2004; Wesley & Buysse, 2004). That being said, many of the documents included in this review reported on the use of pull‐out interventions: a qualitative study done with PTs working in preschool settings revealed that even if they agree with the benefits of in‐context interventions, they still see the need for pull‐out interventions for some children (Sekerak et al, 2003).…”
Section: Discussionmentioning
confidence: 99%